Fuzzy Linear Programming on Portfolio Optimization: Empirical Evidence from FTSE 100 Index (Global Journal of Management and Business Research, 2016)
Portfolio is a list of securities that the investor has. The main objective of portfolio management is to maximize return while minimizing unsystematic risk. Firstly, fundamental definitions are given about theory of fuzzy logic and fuzzy logic approach is stated in this study. In the model of fuzzy logic price/earnings ratio and accumulation/distribution index which are added by the model that Werner improved. Taking all into consideration a new model is developed at the last part of this research.
Keywords: fuzzy linear programming; FTSE 100